Fractionation of 226Ra and Ba in the Upper North Pacific Ocean - van Beek, Pieter; François, Roger; Honda, Makio; Charette, Matthew A.; Reyss, Jean-Louis; Ganeshram, Raja; Monnin, Christophe; Honjo, Susumu (Frontiers in Marine Science, 2022)
Investigations conducted during the GEOSECS program concluded that radium-226 (T1/2 = 1602 y) and barium are tightly correlated in waters above 2500 m in the Atlantic, Pacific and Antarctic Oceans, with a fairly uniform 226Ra/Ba ratio of 2.3 ± 0.2 dpm µmol-1 (4.6 nmol 226Ra/mol Ba). Here, we report new 226Ra and Ba data obtained at three different stations in the Pacific Ocean: stations K1 and K3 in the North-West Pacific and station old Hale Aloha, off Hawaii Island. The relationship between 226Ra and Ba found at these stations is broadly consistent with that reported during the GEOSECS program. At the three investigated stations, however, we find that the 226Ra/Ba ratios are significantly lower in the upper 500 m of the water column than at greater depths, a pattern that was overlooked during the GEOSECS program, either because of the precision of the measurements or because of the relatively low sampling resolution in the upper 500 m. Although not always apparent in individual GEOSECS profiles, this trend was noted before from the non-zero intercept of the linear regression when plotting the global data set of Ba versus 226Ra seawater concentration and was attributed, at least in part, to the predominance of surface input from rivers for Ba versus bottom input from sediments for 226Ra. Similarly, low 226Ra/Ba ratios in the upper 500 m have been reported in other oceanic basins (e.g. Atlantic Ocean). Parallel to the low 226Ra/Ba ratios in seawater, higher 226Ra/Ba ratios were found in suspended particles collected in the upper 500 m. This suggests that fractionation between the two elements may contribute to the lower 226Ra/Ba ratios found in the upper 500 m, with 226Ra being preferentially removed from surface water, possibly as a result of mass fractionation during celestite formation by acantharians and/or barite precipitation, since both chemical elements have similar ionic radius and the same configuration of valence electrons. This finding has implications for dating of marine carbonates by 226Ra, which requires a constant initial 226Ra/Ba ratio incorporated in the shells and for using 226Ra as an abyssal circulation and mixing tracer.